Solid Waste Management System in the Kanifing Municipal Council's Area, the Gambia - Badgie, Dawda (2010)
Pollution by solid waste and its management is an endemic problem that the Government of the Gambia through its municipalities has tried to address over the years but do not seem to bring it under control. Inadequate municipal solid waste management is certainly one of the major contributing factors to the degrading of environment quality. This study was done at Kanifing Municipal Council (KMC), one of the densely populated and rapidly growing urban settlements in The Gambia. The study is meant to determine the ramifications of poor solid waste management, the impact of these on the communities, the problem associated with waste management at KMC and the applicability of integrated solid waste management system (ISWM) in the stated Municipality. A total of 410 questionnaires were distributed and these were administered to households within Kanifing Municipality using systematic random sampling. These were supplemented by personal interviews with the municipal council authorities, and other key stakeholders. The data was analyzed by a non-parametric statistical test such as chi square cross tabulation calculation. The study found that the residents of the area interviewed were reasonably aware of the importance of proper solid waste management in relation to health of the inhabitants, aesthetic value and tourism which needs to be enhanced. Significant challenges were discovered that need to be addressed in future and this include inter alia: low environmental awareness on waste reduction, separation and recycling techniques were discovered as well as; improper enforcement of waste related legislations, inadequate infrastructure, funding and expertise all of which are important when dealing directly with waste management. In general, the study shows that there are high prospects of addressing solid waste management issues in the Kanifing Municipality; however, more efforts are absolutely necessary by both the Municipal Authorities and the Central Government of the Gambia in achieving the set objectives of a clean and beautiful municipality. Key words: Solid waste management system, Pollution, Solid waste,degrading urban environment, Kanifing Municipal council